2021
DOI: 10.1111/ijcp.14963
|View full text |Cite
|
Sign up to set email alerts
|

Clinical‐epidemiological and radiological characteristics of stroke patients: A multicentre study

Abstract: Introduction and Aim Stroke is the leading cause of disability in adults and the second most common cause of death, at a rate of 11.8% worldwide. The purpose of this study was to examine the aetiological, demographic, and clinical characteristics of patients admitted to hospital because of acute strokes. Materials and Methods This multicentre study retrieved information for all patients admitted to hospital because of an acute cerebrovascular event over a six‐month period, and sociodemographic, aetiological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Stroke is a serious health hazard with high mortality and disability rates and has gradually become the leading cause of death in humans ( 30 , 31 ). Approximately 5.5 million stroke-related deaths occur each year ( 32 ). Around 30% of patients with an initial onset of acute cardio-cerebrovascular disease exhibit no clinical symptoms ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a serious health hazard with high mortality and disability rates and has gradually become the leading cause of death in humans ( 30 , 31 ). Approximately 5.5 million stroke-related deaths occur each year ( 32 ). Around 30% of patients with an initial onset of acute cardio-cerebrovascular disease exhibit no clinical symptoms ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral autosomal dominant arteriopathies with subcortical infarcts and leukoencephalopathy (CADASIL) and Fabry disease should be kept in mind [30]. Considering the treatment arrangement in a study performed by Kunt et al [31], examining the clinical and demographic characteristics of patients with stroke, the relationship between medicine use and cerebrovascular events was investigated. It was observed that stroke occurred in 527 patients (46.3%) while using antiaggregant or anticoagulant, and when the medicines used were examined, it was found that significant difference between the patient groups in terms of the use of acetylsalicylic acid, clopidogrel and warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…All air-sensitive reactions were performed under an atmosphere of argon with magnetic stirring. 1 H nuclear magnetic resonance (NMR) and 13…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…Stroke ranks as the second most common cause of death and a leading cause of disability worldwide. 1 It can be categorized into ischemic stroke and hemorrhagic stroke, with the former being more prevalent, accounting for approximately 80% of all stroke cases. 2 Currently, tissue plasminogen activator remains the only Food and Drug Administration-approved drug for treating ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%